VALUE AND MOTIVATIONAL ASPECTS OF PEDAGOGICAL INTERACTION OF TEACHER AND STUDENTS - Muzуka Olena (Educological discourse, 2017)
The article deals with value-motivational aspects of pedagogical interaction of the teacher and students. It turns out that the development of internal motivation and the formation of a sense of competence contributes to the accumulation of positive experience in solving educational and professional tasks in the process of value interaction between the teacher and students. The criteria for mutual evaluation of educational achievements are singled out in order to promote the value comprehension of the future professional activity and the formation of professional competencies. The system of work aimed at developing internal motivation, in conjunction with the psychological atmosphere created in interaction in the systems of "teacher - student" and "student - student", is able to provide self - development of future specialists, their autonomy, competence and personal responsibility for the results of execution educational and professional activity. Accumulation of the experience of successful educational activity contributes to the development of the value sphere of students and the formation of professional competencies.